2019
DOI: 10.1111/evj.13063
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sepsis is rare following intrasynovial medication in equine ambulatory practice

Abstract: Summary Background There are few observational studies regarding the potentially serious complication of synovial sepsis following intrasynovial medication in general equine practice. Quantification of risk is fundamental to fully inform decision‐making and owner consent prior to undertaking procedures. Objectives To describe the occurrence of synovial sepsis following intrasynovial injections in a large ambulatory equine practice between 2006–2011. Study design Retrospective cohort study. Methods Medication r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 15 publications
(42 reference statements)
2
27
0
Order By: Relevance
“…One of the included studies provided weak evidence of an increased risk of synovial sepsis following the injection of PSGAGs. Smith et al (2018) reported that injection of PSGAGs was positively associated with iatrogenic synovial sepsis, though this finding was not statistically significant. In an abstract found in the literature search (though not included in the Knowledge Summary as it was an unpublished proceedings expanded abstract), Bohlin et al (2014) also reported that injection of PSGAGs in combination with corticosteroids appeared to increase the risk of infection.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 94%
See 1 more Smart Citation
“…One of the included studies provided weak evidence of an increased risk of synovial sepsis following the injection of PSGAGs. Smith et al (2018) reported that injection of PSGAGs was positively associated with iatrogenic synovial sepsis, though this finding was not statistically significant. In an abstract found in the literature search (though not included in the Knowledge Summary as it was an unpublished proceedings expanded abstract), Bohlin et al (2014) also reported that injection of PSGAGs in combination with corticosteroids appeared to increase the risk of infection.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 94%
“…Of the three studies examined, only two studies directly evaluated the prevalence of iatrogenic synovial sepsis following intra-articular injection. Two out of the three studies were retrospective analyses of medical records (Smith et al, 2018 andSteel et al, 2013) and one was a survey based study with retrospective analyses of medical records submitted by questionnaire respondents (Gillespie et al, 2016). The searches also revealed an abstract by Smith et al (2013) which was later published as a full study (Smith et al, 2018) and for the purposes of avoiding data replication, only the full study has been included.…”
Section: The Evidencementioning
confidence: 99%
“…The search gave a lot of results, as it was not very specific, but it makes sure that relevant publications were not missed. However, only two publications related to the PICO question were found and one publication (Smith et al 2018) was mentioned by a reviewer but was not picked up in the searches due to search query restrictions. One paper was a cross-sectional study and the other two were retrospective cohort studies, one of which includes a case-control design.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%
“…None of these publications respond directly to the PICO question, but the authors looked at the result of using antimicrobials in addition to intra-articular injections of corticosteroids. In general, the risk of sepsis after intra-articular injections is very low -7.8 cases per 10,000 injections (Steel et al 2013) or 2.1 cases per 10,000 injections (Gillespie et al 2016) or 4.2 cases per 10,000 injections (Smith et al 2018). The veterinarian and type of corticosteroid were identified as risk factors (Steel et al 2013).…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%
“…This retrospective study by Lewis Smith and colleagues in the UK aimed to determine the incidence of synovial sepsis following intrasynovial medication in a single UK ambulatory practice .…”
Section: Synovial Sepsismentioning
confidence: 99%